2005
DOI: 10.1167/iovs.04-0649
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor-β2 Modulated Extracellular Matrix Component Expression in Cultured Human Optic Nerve Head Astrocytes

Abstract: TGF-beta 2 is capable of inducing the expression of ECM and basement membrane components in cultured ONH astrocytes via CTGF and upregulated TSP-1, a protein naturally involved in the activation of latent TGF-beta. Therefore, TGF-beta 2 could be a factor in the initiation of the modification of ECM in the glaucomatous ONH. In addition, TSP-1 induction may be a mechanism by which TGF-beta 2 amplifies its own activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
105
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(111 citation statements)
references
References 34 publications
5
105
0
1
Order By: Relevance
“…It is reported that intracellular SMAD signaling induces expression of extracellular matrix (ECM) and basement membrane components in cultured astrocytes via Type IV pro-collagens (Fuchshofer et al, 2005;Gaussin, 2002;Jackson et al, 2003). ECM components regulated by SMAD signaling direct remodeling of blood vessels in some internal organs such as the lung or liver (Ng et al, 2005;Fernandez-L A, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that intracellular SMAD signaling induces expression of extracellular matrix (ECM) and basement membrane components in cultured astrocytes via Type IV pro-collagens (Fuchshofer et al, 2005;Gaussin, 2002;Jackson et al, 2003). ECM components regulated by SMAD signaling direct remodeling of blood vessels in some internal organs such as the lung or liver (Ng et al, 2005;Fernandez-L A, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…TGF-␤2 has been reported to induce fibronectin, collagen type I, and collagen type IV in both human retinal pigment epithelial cell line and cultured human optic nerve head astrocytes. 23,24 TGF-␤3 has also been reported to decrease matrix metalloproteinase-2 (MMP-2) and increase tissue inhibitor of metalloproteinase-1 (TIMP-1) and collagen type I in primary lung fibroblasts. 25 All three TGF-␤ isoforms have been reported to activate the TGF-␤ signaling pathway via Smad2 activation.…”
Section: Discussionmentioning
confidence: 99%
“…Biologically active CTGF is both secreted and expressed on the cell membrane (19,20). Conditioned medium prepared from 4F1 cells had prominent expression of CTGF compared with control 4V cells (Fig.…”
Section: Growth Inhibition Of Nsclc Cells By Ctgf Overexpressionmentioning
confidence: 97%